ANALYSIS STUDY SETTLEMENT IN CLAY OF SOFT AND CLAY OF ORGANIC USE MODELING BOX AND MATRASS CONCRETE BENDRAT WITH A POLE - sukamto, yusuf; Afriani, Lusmeilia; adha, idarmahadi (Universitas Lampung, 2017)
This research make modeling box test for testing land subsidence and treatment the testing on the ground had been given bracing of using a concrete mat bendrat with the piling softwood on the organic clay and soft clay soil. It will were laden starting from 0,2 kg/cm2, 0,3 kg/ cm2, 0,4 kg/cm2, 0,5 kg/cm2. Testing in the physical properties that is water content, specific gravity, sieving, hidrometri, atterberg limits and mechanical testing such as consolidation test and consolidation box test.On the research of testing the physical properties of soil from belmibing sari village is soft clay soil and from Benteng Sari village is organic clay. Based on the result of mechanical testing on consolidating the lab test with test box that the results of the test above state the value of test Cc box test is lower because test box use bendrat concrete reinforcement mat with a pole softwood, that matter can be concluded that carrying capacity on the clay become more stable because hollow cavities in the soil pore filled with particles interlocking so the ground is being easily compressible if gets pressures from the inflicting, soil degradation that occurs will be reduced. So as to reduce the risk of damage of construction on top of it .Password: soil settlement, organic clay , soft clay .